The post activation potentiation effects of plyometric exercises on jump performance in well-trained gymnasts - Dallas, G.; Paradisis, G.; Pappas, P.; Tsolakis, C. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Plyometric training has been used as a warm-up method in order to improve subsequent power and strength especially in the sports of gymnastics. Drop jump (DJ) is a task that includes the so-called stretch-shortening cycle (SSC), where an eccentric contraction precedes a concentric contraction. The purpose of this study was to examine the acute post activation pontetiation effects of different plyometric exercises on drop jump performance in well trained gymnasts. Methods: Thirty-five male and female well trained gymnasts (age 20.37 ± 4.20 years, body mass 58.41 ± 10.14 Kg, height 1.66 ± 0.09 m) volunteered to participate in this study. The condition stimuli were two different plyometric exercises (Rondat & Tuck jumps) performed under two separate visits to assess drop jump performance. A Pre test performed before the start of the intervention program which consisted of 1 set of 10 Rondats and 2 set of 5 tuck jumps (TJ). A post test was performed immediately after and 3 mins (Post 3), 6 mins (Post 6) and 9 mins (Post 9) after the end of the intervention program. Results: Significant DJ height main effects for time and gender were found indicating that men performed better than women and that DJ height was increased over time. Further, a time x gender DJ height main effect for time was found and the Post hoc analyses for DJ height comparing the baseline values showed large differences immediately after and after 6 and 9 min for males and immediately after, remaining unchanged thereafter for females respectively. Discussion: Both plyometyric exercises had a positive effect on drop jump performance (Hilfiker et al, 2007), throughout the rest interval range of 1-9 minutes in the male gymnasts, with no change in performance in the female gymnasts. Plyometric exercises were effective warm-up methods and produce PAP effect thus performance was improved.